Jaina logic: a model-based analysis of the seven predications - López Astorga, Miguel (Círculo de Lingüística Aplicada a la Comunicación, 2023)
A relevant part of Jainism is its logic. Jaina logic gives tools to communicate and argue. However, it is problematic from the western perspective: it seems to be a paraconsistent system, that is, a system in which a fact and the denial of that very fact can be true at once. Those difficulties have been overtaken from interpretations that ignore classical standard logic and assess Jaina logic from a point of view more linked to reasoning and the real use of natural language. One of those interpretations have resorted to the theory of mental models, and that interpretation is the one the present paper develops. This is because the theory of mental models has been updated and, hence, any relation provided between Jaina logic and this last theory should be updated as well.